2022
DOI: 10.3389/fnins.2021.791510
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of the Processes of Autonomic Control of Blood Circulation in Humans Is Different in the Awake State and in Sleep Stages

Abstract: The influence of higher nervous activity on the processes of autonomic control of the cardiovascular system and baroreflex regulation is of considerable interest, both for understanding the fundamental laws of the functioning of the human body and for developing methods for diagnostics and treatment of pathologies. The complexity of the analyzed systems limits the possibilities of research in this area and requires the development of new tools. Earlier we propose a method for studying the collective dynamics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…However, the interaction between respiration and the low-frequency component of a heart rhythm, which is associated with the process of autonomic control of blood circulation, also plays an important role in the cardiorespiratory interaction. It has been shown that this type of cardiorespiratory interaction is important in studies of sleep [10][11][12] and healthy aging [13][14][15][16], in the assessment of psychophysiological state [17], in the prediction of complications of cardiovascular diseases [18,19], and in basic research [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the interaction between respiration and the low-frequency component of a heart rhythm, which is associated with the process of autonomic control of blood circulation, also plays an important role in the cardiorespiratory interaction. It has been shown that this type of cardiorespiratory interaction is important in studies of sleep [10][11][12] and healthy aging [13][14][15][16], in the assessment of psychophysiological state [17], in the prediction of complications of cardiovascular diseases [18,19], and in basic research [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the strength and structure of couplings between such processes is a useful tool for constructing quantitative indices that characterize changing physical and psychophysiological states [4][5][6][7]. Methods for detecting the interaction of various body systems have been successfully applied to the estimation of the biological age [8,9], classification of sleep stages [10][11][12], diagnosis of the severity of diseases of the cardiovascular system [13][14][15], and stress diagnosis [5,7,16]. The latter is important for the implementation of continuous monitoring of the stress level in everyday life and the identification of people at risk of developing stress-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the study of brain activity during changes in the psycho-emotional state is carried out in the following frequency ranges: delta (0.5-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12)(13), beta (14-30 Hz), and gamma . At the same time, the analysis of infra-slow oscillations of brain potentials with a frequency of less than 0.5 Hz can provide important additional information for diagnosing the development of stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation